Usefulness of microchip electrophoresis for the analysis of mitochondrial DNA in forensic and ancient DNA studies - Alonso, A (2006)
We evaluate the usefulness of a commercially available microchip CE (MCE) device in different genetic identification studies performed with mitochondrial DNA (mtDNA) targets, including the haplotype analysis of HVR1 and HVR2 and the study of interspecies diversity of cytochrome b (Cyt b) and 16S ribosomal RNA (16S rRNA) mitochondrial genes in forensic and ancient DNA samples. The MCE commercial system tested in this study proved to be a fast and sensitive detection method of length heteroplasmy in cytosine stretches produced by 16 189T>C transitions in HVR1 and by 309.1 and 309.2 C-insertions in HVR2. Moreover, the quantitative analysis of PCR amplicons performed by LIF allowed normalizing the amplicon input in the sequencing reactions, improving the overall quality of sequence data. These quantitative data in combination with the quantification of genomic mtDNA by real-time PCR has been successfully used to evaluate the PCR efficiency and detection limit of full sequencing methods of different mtDNA targets. The quantification of amplicons also provided a method for the rapid evaluation of PCR efficiency of multiplex-PCR versus singleplex-PCR to amplify short HV1 amplicons (around 100 bp) from severely degraded ancient DNA samples. The combination of human-specific (Cyt b) and universal (16S rRNA) mtDNA primer sets in a single PCR reaction followed by MCE detection offers a very rapid and simple screening test to differentiate between human and nonhuman hair forensic samples. This method was also very efficient with degraded DNA templates from forensic hair and bone samples, because of its applicability to detect small amplicon sizes. Future possibilities of MCE in forensic DNA typing, including nuclear STRs and SNP profiling are suggested.